SYSTEMS FOR MONITORING GOODS IN THE SLOVAK INLAND TRANSPORTATION (Perner's Contacts, 2018)
Intelligent transport systems, used for tracking of goods, open up new opportunities to achieve sustainable mobility and create the conditions for a high-quality communication and information society. The paper informs about the tracking systems used in each transport department of Slovakia.
Keywords: tracking system, monitoring, RFID